THE IDEAS OF TRANSCENDENTALISM IN THE WORKS OF EMILY DICKINSON (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article focuses on the analysis of Emily Dickinson's poems, and the elements of transcendentalism in her poetry are discussed separately. First of all, in this article, the unique features of the poet's work are emphasized, and the character traits of the transcendentalism stream are expressed separately. All the sources shown in the article are scientifically proven sources and are explained through examples. Although the concept of “transcendentalism” is a difficult word, it shows a very simple idea. The representatives of this stream are such people who describe the world and nature as they are. They approach the definition of something without excessive decorations and exaggerations. Emily Dickinson is one such writer. In particular, she avoided perfecting the depiction of nature.